Implementation of P5-Based Differentiated Learning in Islamic Religious Education Subjects in Elementary Schools - Agus Hasan; Aisyah Alief Dzulfiqrah; Fitri Nurlaeli; Tarsono Makmuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education is a process to fully develop individual potential, preparing skilled Human Resources who are able to compete globally. Education is the spearhead of civilization, as it is the key to solving every problem. The heart of education is the curriculum, which provides the framework for learning. It encompasses educational goals, content to be taught, as well as teaching methods and techniques. In Indonesia, these efforts are embodied in the Merdeka Curriculum. Implemented since 2021, the Merdeka Curriculum aims to create active and creative learning, and to give students the freedom to develop their potential according to their interests. One of its approaches is differentiated learning based on the Strengthening the Profile of Pancasila Students Project (P5), which tailors the learning system to the needs, interests, and abilities of students. This study analyzes the implementation of differentiated learning based on P5 in Islamic Religious Education subjects in elementary schools. The research employs a mixed methods approach with an embedded design. The results show that this method is effective in increasing learning motivation, understanding of the material, and engagement in learning across all student ability groups. Although there were no significant differences between high, medium, and low ability groups, the trend indicated that high-ability students were more motivated and better understood the material. The main challenges for teachers include the lack of time to prepare materials and the difficulty of managing classes with diverse levels of understanding. Teachers need to provide additional support and simpler instructions to low-ability students. Overall, differentiated learning based on P5 helps students become active, creative, and engaged in learning, while supporting the formation of Pancasila student profile values.